Impact of K+ Doping on Modulating Majority Charge Carrier Type and Quality of Perovskite Thin Films by Two-step Solution Method for Solar Cells - Yao, Yujun; Zou, Xiaoping; Cheng, Jin; Ling, Tao; Chang, Chuangchuang; Chen, Dan (Coatings (Basel), 2019)
Traditional hetero-junction perovskite solar cells are composed of light-absorbing layers, charge carrier-transporting layers, and electrodes. Recently, a few papers on homo-junction perovskite solar cells have been studied. Here, we studied the effect of K+ doping on TiO2/PbI2 interface quality, perovskite film morphology, photo-physical properties, and majority carrier type. In particular, the K+ extrinsic doping can modulate the majority carrier type of the perovskite thin film. The study indicated that the interface between the perovskite layer and the TiO2 layer deteriorates with the increase of K+ doping concentration, affecting the electron transport ability from the perovskite film to the TiO2 layer and the photo-physical properties of the perovskite layer by K+ doping. In addition, the majority charge carrier type of perovskite thin films can be changed from n-type to p-type after K+ extrinsic doping, and the corresponding hole concentration increased to 1012 cm−3. This approach of modulating the majority charge carrier type of perovskite thin film will pave the way for the investigation of perovskite homo-junction by extrinsic doping for solar cells.